The Role of the Moraxella catarrhalis CopB Protein in Facilitating Iron Acquisition From Human Transferrin and Lactoferrin - Chan, Clement; Ng, Dixon; Schryvers, Anthony B. (Frontiers in Microbiology, 2021)
Moraxella catarrhalis is a Gram-negative bacterium that is responsible for a substantial proportion of upper respiratory infections in children and lower respiratory infections in the elderly. M. catarrhalis resides exclusively on the mucosal surfaces of the upper respiratory tract of humans and is capable of directly acquiring iron for growth from the host glycoproteins human transferrin (hTf) and human lactoferrin (hLf). The iron-bound form of these glycoproteins is initially captured by the surface lipoproteins Tf or Lf binding protein B (TbpB or LbpB) and delivered to the integral outer membrane TonB-dependent transport (TBDT) proteins, Tf binding protein A (TbpA) or Lf binding protein A (LbpA). The extraction of iron involves conformational changes in Lf and Tf to facilitate iron removal followed by its transport across the outer membrane by a well characterized process for TBDTs. Surprisingly the disruption of the gene encoding another TBDT, CopB, results in a reduction in the ability to grow on human Tf or Lf. The possibility that this could have been due to an artefact of mutant construction that resulted in inhibition of TonB-mediated process was eliminated by a complete deletion of the CopB gene. A systematic evaluation of the impact on growth under various conditions by deletions of the genes encoding TbpA, LbpA and CopB as well as mutations of the iron liganding residues and TonB box region of CopB was implemented. The results indicate that although CopB is capable of effectively acquiring iron from the growth medium, it does not directly acquire iron from Tf or Lf. We propose that the indirect effect on iron transport from Tf and Lf by CopB could possibly be partially explained by the association of TBDTs at gaps in the peptidoglycan layer that may enhance the efficiency of the process. This concept is supported by previous studies demonstrating an indirect effect on growth of Tf and Lf by deletion of the peptidoglycan binding outer membrane lipoprotein RmpB in Neisseria that also reduced the formation of larger complexes of TBDTs.